2021
DOI: 10.3390/ijerph18126483
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health-Related Quality of Life among Croatian University Students

Abstract: Oral health-related quality of life (OHRQoL) is utilized in health services research to examine trends in oral health and population-based needs assessment. To determine the impact of oral diseases on everyday life, measures of oral quality of life are needed. In addition to common disease-based measures, they assess the need for oral care to evaluate oral health care programs and treatment management. The aim of this study was to evaluate the OHRQoL among Croatian university students. A cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…The OHIP-14 has been widely applied in different samples and contexts. Given the different proposals for factor structures for OHIP-14 [ 16 , 18 ], We used the CFA method to evaluate the fit of different factorial models of the OHIP-14 (3-factor model, 4-factor model, and 7-factor model) for Chinese University Students before testing measurement invariance [ 37 ]. Model fit was estimated using the χ 2 statistic, the comparative fit index (CFI), the Tucker–Lewis index (TLI), standardized root mean square residual (SRMR), and the root means the square error of approximation (RMSEA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OHIP-14 has been widely applied in different samples and contexts. Given the different proposals for factor structures for OHIP-14 [ 16 , 18 ], We used the CFA method to evaluate the fit of different factorial models of the OHIP-14 (3-factor model, 4-factor model, and 7-factor model) for Chinese University Students before testing measurement invariance [ 37 ]. Model fit was estimated using the χ 2 statistic, the comparative fit index (CFI), the Tucker–Lewis index (TLI), standardized root mean square residual (SRMR), and the root means the square error of approximation (RMSEA).…”
Section: Methodsmentioning
confidence: 99%
“…A set of 3 underlying factors, like functional limitation, pain discomfort, and psychosocial impacts, were confirmed by Javier Montero et al [ 17 ]. Recent studies have confirmed the adequacy of the original factorial structure, the 7-factor structures of OHIP-14 among university students [ 18 ]. It illustrated the need to explore appropriate structural factors for the OHIP-14 scale to make sure that it is utilized as an important tool for assessing OHRQoL.…”
Section: Introductionmentioning
confidence: 91%
“…The responses to all 14 questions were summed up to determine the overall OHIP-14 score, which ranges from 0 to 56. The higher the OHIP-14 score, the worse the OHRQoL [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…17 Nilai OHRQoL mencerminkan kenyamanan individu saat makan, tidur, dan hal ini terlihat dalam interaksi sosial, harga diri dan kepuasan sehubungan dengan kesehatan gigi dan mulut, 18 serta digunakan untuk mengetahui dampak penyakit rongga mulut terhadap kehidupan sehari-hari yang diperlukan untuk mengukur kualitas hidup terkait kesehatan gigi dan mulut. 19…”
Section: Pendahuluanunclassified